1988
DOI: 10.3853/j.0067-1975.40.1988.154
|View full text |Cite
|
Sign up to set email alerts
|

Glypturus motupore, a new callianassid shrimp (Crustacea: Decapoda) from Papua New Guinea with notes on its ecology

Abstract: A new callianassid shrimp, Glypturus motupore, is described from Papua New Guinea and compared with G. acanthochirus, G. armatus and G. laurae, three similar species of the genus from the Caribbean and Indo-West Pacific. Glypturus motupore is found intertidally and subtidally to depths of 30 m. The species processes large quantities of sediment and subtidally builds volcano-shaped mounds up to 46 cm high. Burrows are complex, extending up to 1.5 m deep and 2 m laterally. Burrows are lined with fine-grained sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 5 publications
2
13
1
Order By: Relevance
“…The funnel-shaped burrows of Chasmagnathus granulatus with low aspect ratio (depth/diameter < 1) exemplify a common entrance shape among burrowing species, and have been suggested to work as a sediment trap in other thalassinidean shrimps (Suchanek 1983, Poore & Suchanek 1988, Witbaard & Duineveld 1989, Vaugelas 1990, Nickell & Atkinson 1995. Our results confirm that these burrows are efficient bedload collectors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The funnel-shaped burrows of Chasmagnathus granulatus with low aspect ratio (depth/diameter < 1) exemplify a common entrance shape among burrowing species, and have been suggested to work as a sediment trap in other thalassinidean shrimps (Suchanek 1983, Poore & Suchanek 1988, Witbaard & Duineveld 1989, Vaugelas 1990, Nickell & Atkinson 1995. Our results confirm that these burrows are efficient bedload collectors.…”
Section: Discussionsupporting
confidence: 76%
“…However, based on the heuristic model proposed by Suchanek (1985), the architecture of C. granulatus burrows reflects variations in trophic modes associated with sediment structure (Iribarne et al 1997). According to this model, burrows with funnel shape entrances favor deposit feeding because they work as sediment traps by enhancing capture of bedload-transported particles that slip down the sides of the funnel (Suchanek 1983, Poore & Suchanek 1988, Witbaard & Duineveld 1989, Vaugelas 1990, Nickell & Atkinson 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete casts made by Curran at the Bahamas (personal communication in Vaugelas, 1990) closely resemble the burrows described here and can be attributed to G. acanthochirus. A similar burrow shape have been reported for G. laurae (Vaugelas and Saint Laurent, 1984;Vaugelas, , 1990, G. motupore (Poore and Suchanek, 1988;Suchanek personal communication, 1989 andin Vaugelas, 1990) and G. armatus (Vaugelas, personal communication 1987;Vaugelas, 1990). Similar in shape are also the burrows of Callianassa sp.…”
Section: Glypturus Acanthochirussupporting
confidence: 49%
“…Surface mounds (Feature 1) are caused by removal of sediment from the burrow to the surface and, apart from during burrow construction, are indicative of a deposit feeding trophic mode. The origin of this sediment, however, can be either surface, as for some tropical callianassid species using the burrow as a sediment trap (Suchanek 1983, Poore & Suchanek 1988, Vaugelas 1990 and as speculated for C. subterranea from the North Sea (Witbaard & Duineveld 1989), or subsurface, as for C. subterranea from the present study.…”
Section: Classification Of Thalassinidean Burrow Morphologymentioning
confidence: 71%
“…Suchanek et al (1986) resin cast burrows of an unidentified callianassid species from a tropical lagoon. They suggested that the burrow was acting as a sediment trap, a hypothesis supported by other authors (Suchanek 1983, Poore & Suchanek 1988, Witbaard & Duineveld 1989, Vaugelas 1990. Particles falling or subducted into the funnel-shaped openings by animalgenerated currents may be used directly or indirectly (via the growth of micro-organisms) as food.…”
Section: Functional Morphology Of Burrows Callianassa Subterraneamentioning
confidence: 72%